TINDAK KEKERASAN DALAM RUMAH TANGGA ( MENCARI MODEL PENANGANAN PEMERINTAH, LSM DAN MASYARAKAT UNTUK PERLINDUNGAN HUKUM KORBAN KEKERASAN DALAM RUMAH TANGGA) - Sigit Irianto (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2010)
Household violence has been a national and global problem. Women are often considered depending much on men and their autonomous characteristics are reduced. Therefore realization of justice and gender equality between men and women is not merely an issue and a women's demand any longer. In Indonesia protection on women is regulated in the Law No. 23/2004. However household violence still happens either in the aspects of physical, psychological, sexual or economic violence.The result of research can be exposed that the forms of household violence that are distinguished among physical, psychological, sexual and economic violence, actually in the field show that the forms of the violence can be an inseparable sequence. There has not been a good coordination among the government, non-government organization and society in implementing the Law. Regulations in the forms of either regulation, instruction, or the decree of Regional Head on legal protection to handle household violence in the levels of either Province or Regency/Municipality have been made, but they have not been running optimally. Based on above research result, the researcher draws a conclusion that the implementation of the Law No. 23/2004 and the other regulations related to women protection has not been effective so that it is necessary to create a model of cooperative network to handle household violence among the government, non government organization and society